PENGARUH PENGGUNAAN MATERI BACAAN BERBASIS KEARIFAN LOKAL PADA MATA KULIAH READING FOR INFORMATION - Sukmawati Yasim; Rusdiah Andalucia (LP2M IAIN Sultan Amai Gorontalo, 2018)
This research aims to know (1) how significant the influence of reading text based on local wisdom in reading for information subject; (2) students’ perception on using reading text based on local wisdom in reading for information subject. The population of this research was the second semester of students of English Education Department, social and Politic science Faculty, Western Sulawesi University by taking 50 students as samples. The research method was pre-experimental design, with pre-test, six times of treatment, and post-test. Data was collected through multiple choice and questionnaire. Data analaysis used SPSS. The result shows that t-test score and students’ score in post-test was p< 0.05. There was significant differences of students’ score between pre-test and post-test after the treatment with reading text based on local wisdom in Reading for Information subject. Questionaire analysis shows that students’ perception on material using was influencing.